Control of Tungsten Protrusion with Surface Active Agent during Tungsten Chemical Mechanical Polishing. (29th November 2017) - You, Keungtae; Seo, Jihoon; Kim, Patrick Joo Hyun; Song, Taeseup
Abstract : With shrinkage of the minimum feature size to sub-14 nm, protrusion/dishing issues in chemical mechanical planarization (CMP) processes have become increasingly important to address. In this study, we propose an advanced slurry formulation with a surface active agent to prevent W protrusion during the W CMP process. In the presence of surface active agent, blanket removal rates on both W and SiO2 films showed non-Prestonian behavior at a low threshold pressure, which is explained by adsorption characteristics of the surface active agent on the films. To study the effect of the surface active agent on W protrusion, W-patterned wafers were polished at the threshold pressure. As the concentration of the surface active agent increased from 0 to 12 mM, W protrusion from patterns with line/space widths of 0.5 μm/0.5 μm decreased significantly from 186 to 30 Å. The mechanism on the significant decrease in W protrusion behavior in the presence of the surface active agent is discussed.